A Communication Based Islanding Detection Method for Photovoltaic Distributed Generation Systems. (23rd July 2014) - Bayrak, Gökay; Cebeci, Mehmet
Abstract : PV based distributed generation (DG) systems must have some electrical connection standards while they connected to an electrical grid. One of these electrical conditions and the most important one is unplanned islanding condition. Islanding is a very dangerous condition because it could damage the PV system and related electrical systems and also working people have been at risk in islanding condition. In this application study, a new communication based islanding detection method was introduced for grid tied PV systems. A real time controller was developed with Labview for detecting islanding condition. Developed method is a hybrid method which uses the effective ways of communication based and passive methods. The results obtained from the proposed real time islanding detection method show that proposed method is reliable, robust, and independent from load and inverter. Nondetection zone (NDZ) is almost zero and islanding detection time is approximately 1-2 cycles indicated in experimental results so this time has a significant short response time according to IEEE 929-2000 standard. The proposed method is effective and presents a realistic solution to islanding so it could be implemented easily to grid tied PV systems and could be used in real system applications.